2015
DOI: 10.3357/amhp.ec08.2015
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Intolerance After ISS and Space Shuttle Missions

Abstract: The proportion of ISS astronauts who could not complete the OTT on R+0 was greater and the recovery rate slower after ISS compared to Shuttle missions. Thus, mission planners and crew surgeons should anticipate the need to tailor scheduled activities and level of medical support to accommodate protracted recovery after long-duration microgravity exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 0 publications
3
66
0
Order By: Relevance
“…The Recovery from Fall/Stand Test as described above was also used to acquire cardiovascular system parameters by collecting electrocardiogram and blood pressure data continuously throughout the test. Previous data collected in astronauts returning from long-duration missions suggested that the earliest signs of presyncope in orthostatically intolerant astronauts ( n = 5) did not occur until 5.5 min into a passive head-up tilt test ( 3 ). Hence, a 3.5-min operational version of the stand test used in an earlier investigation ( 20 ) was used to standardize a submaximal stressor of the cardiovascular system while (a) minimizing the risk of subjects developing presyncopal symptoms, (b) meeting testing time requirements, and (c) ensuring the ability for subjects to complete the remainder of the study.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Recovery from Fall/Stand Test as described above was also used to acquire cardiovascular system parameters by collecting electrocardiogram and blood pressure data continuously throughout the test. Previous data collected in astronauts returning from long-duration missions suggested that the earliest signs of presyncope in orthostatically intolerant astronauts ( n = 5) did not occur until 5.5 min into a passive head-up tilt test ( 3 ). Hence, a 3.5-min operational version of the stand test used in an earlier investigation ( 20 ) was used to standardize a submaximal stressor of the cardiovascular system while (a) minimizing the risk of subjects developing presyncopal symptoms, (b) meeting testing time requirements, and (c) ensuring the ability for subjects to complete the remainder of the study.…”
Section: Methodsmentioning
confidence: 98%
“…Multiple studies have demonstrated that exposure to spaceflight produces adaptations in sensorimotor, cardiovascular, and neuromuscular systems that are maladaptive upon return to 1 g . These adaptations are often manifested in balance and gait disturbances ( 1 , 2 ), cardiovascular deconditioning ( 3 , 4 ), and loss of muscle mass, muscle coordination, and strength ( 5 7 ). For example, mobile mission tasks after landing on a planetary surface may include a rapid egress from a vehicle.…”
mentioning
confidence: 99%
“…Accordingly, to evaluate the VCR uncorrected by the baroreflex, we examined early HUT-induced BP response (1–20 s) for a total HUT duration of 2 min. This procedure did not allow us to evaluate orthostatic intolerance, which, in astronauts, is typically evaluated by a 10-min stand test 11 16 . Thus, we could not conclude whether the impaired VCR contributes to orthostatic intolerance, which represents a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the vestibular system is known to be highly plastic, i.e., its sensitivity might be altered if the subject is exposed to a different gravitational environment. Understanding the plasticity of the vestibular system and its effect on vestibular-mediated functions is essential in the study of microgravity-induced medical complications such as body instability, orthostatic hypotension, muscle atrophy, and bone loss; these conditions are major complications associated with spaceflight 11 12 13 14 15 16 and should be addressed before assigning astronauts on space missions that require traveling longer distances or spending longer periods of time under microgravity conditions.…”
mentioning
confidence: 99%
“…Blood redistribution is thought to be the key initiating event for cardiovascular adaptation to weightlessness (Watenpaugh and Hargens, 1996), followed by a decrease in blood volume (Johnson, 1979), due to loss of plasma (Smith et al, 1997) and erythrocytes (Ivanova et al, 2007;Noskov et al, 1991;Poliakov et al, 1998;Tavassoli, 1982), an increase of stroke volume (Norsk et al, 2015), and alterations of heart rate (Baevsky et al, 1997;Karemaker and Berecki-Gisolf, 2009;Verheyden et al, 2009) and central blood pressure regulation (Baevsky et al, 2007;Di Rienzo et al, 2008;Fritsch et al, 1992;Morita et al, 2016;Pagani et al, 2009). While these changes of cardiovascular functions pose no threat during the space flight, after landing the cardiovascular system is no longer capable to sustain normal blood pressure while standing Kotovskaya and Koloteva, 2016;Lee et al, 2015) or with other loads (Fu et al, 2004;Levine et al, 1996). Time and medical aid suffice to overcome the post-flight cardiovascular disadaptation on Earth (Laughlin et al, 2015;Payne et al, 2007;Vasilyeva and Bogomolov, 1991), but after landing on other planets both might be limited and thus disadaptation of the cardiovascular system might restrict the ability of cosmonauts/astronauts to work in this busy period.…”
Section: Introductionmentioning
confidence: 99%